2021
DOI: 10.1556/204.2021.00015
|View full text |Cite
|
Sign up to set email alerts
|

The future plans and dilemmas of Chinese students studying in Hungary: A narrative analysis

Abstract: Studying in Hungary has become a new trend among Chinese students under the Belt and Road Initiative. The spectacular tripling of the growth of incoming Chinese students has influenced the number of international students in Hungary. In this paper, 26 in-depth narrative interviews with Chinese students in Hungary were conducted and analysed, employing the grounded theory method. This research reveals that beyond considerable uncertainty regarding future plans and career trajectories, three paths are open for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Additionally, there is a growing number of fee-paying Chinese students. Li and Primecz (2021) suggested that Chinese students studying in Hungary contribute to the development of beneficial networks between Hungary and China. Hungary, a non-English speaking nation, is seeing an increase in Chinese students for a variety of reasons: (1) the Stipendium Hungaricum scholarship promotes proficiency in both English and Hungarian, a critical component of international educational mobility; (2) the majority of Hungarian educational institutions offer language-training programmes to assist international students who do not meet language requirements to begin their academic studies and thus provide a 'bridge', with particular emphasis on incoming Chinese students, in relation to becoming acquainted with the necessary academic skills and adjusting to the local culture; (3) the Hungarian education platform promotes academic mobility to other European regions and the entire world through programmes such as the CEMS Master's in International Management (CEMS Global Alliance).…”
Section: The Bologna Process and Educational Mobility With Respect To...mentioning
confidence: 99%
“…Additionally, there is a growing number of fee-paying Chinese students. Li and Primecz (2021) suggested that Chinese students studying in Hungary contribute to the development of beneficial networks between Hungary and China. Hungary, a non-English speaking nation, is seeing an increase in Chinese students for a variety of reasons: (1) the Stipendium Hungaricum scholarship promotes proficiency in both English and Hungarian, a critical component of international educational mobility; (2) the majority of Hungarian educational institutions offer language-training programmes to assist international students who do not meet language requirements to begin their academic studies and thus provide a 'bridge', with particular emphasis on incoming Chinese students, in relation to becoming acquainted with the necessary academic skills and adjusting to the local culture; (3) the Hungarian education platform promotes academic mobility to other European regions and the entire world through programmes such as the CEMS Master's in International Management (CEMS Global Alliance).…”
Section: The Bologna Process and Educational Mobility With Respect To...mentioning
confidence: 99%
“…Since 2011, China has been Germany's top source of international students, and the number has increased annually. During the winter semester of 2020/21, approximately 40,000 Chinese students were enrolled in German universities [ 2 ]. The increasing influx of international students is regarded as a significant cultural and economic contribution to the host country [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%